Barriers to Development in Orissa - Fox, Calvin (Journal of Soil and Water Conservation, 2022)
Some people understand that the basic problem is low soil fertility, but for fewer people know how to correct the soil fertility problem without spending huge amount of money. The jungle accomplishes this monumental task with the biomass cycle. Amazon jungle is its perfect example. As long as the biomass cycle is not disturbed the one cm. of top soil is constantly replinished by the biomass cycle as the plants use it and the eco-sytem florishes. The Slopy Agricultural Land Technology in Phillipines on low producing soil and in three to five years, yield has jumped from 500 to 2000 Kgs per hectare and continue to climb slowly until this picked at approximately 3000 Kgs per hectare. There is need for an eco-system fertility test. Wasteland can be restored to food production observed in the Phulbani district of Orissa with the meager resource of substances level farmers. Unless the biomass cycle is restablished and protected, ultimately the entire ecosystem will shut down, the area will depopulate and all development will be lost. The most imporatant is controlled rainwater runoff which will stop 90 to 100 per cent of the decaying biomass and every significant amounts of the farmers ' best soil will be protected from loss.